Religiosity and External Whistleblowing Intention - Tuan Mastiniwati Tuan Mansor; Akmalia M. Ariff; Abdul Hafaz Ngah; Hafiza Aishah Hashim (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research paper Research aims: This study explores the role of religiosity in external whistleblowing intention by extending the attitude-behavioural-context (ABC) theory to the whistleblowing context in Malaysia. A Muslim has the responsibility to report any wrongdoing in their organisation to protect public interest, as part of amr bil ma‘ruf wa nahy ‘anil munkar, or enjoining good and forbidding evil. Design/Methodology/Approach: This study utilises a structured questionnaire involving 185 Muslim auditors in Malaysia. A purposive non-probability sampling technique was used, and the data was analysed using SmartPLS 3.3.3. Research findings: The results reveal that religiosity positively influences the perceived control, self-efficacy, and external whistleblowing intention of Muslim auditors, but found no evidence to support the hypotheses related to their attitudes. Further, perceived control and self-efficacy are shown to positively influence attitude.Theoretical contribution/Originality: From the perspective of the ABC theory, the findings suggest that self-efficacy and perceived control are the contextual factors that strongly influence external whistleblowing, and that religiosity can be added to extend the ABC theory in the whistleblowing context. Practitioner/Policy implications: The findings are valuable to audit firms in understanding the effect of religiosity to Muslim auditors to reveal wrongdoings in their firms. Research limitation/Implications: This study is among the first to use ABC theory to examine religiosity in the context of whistleblowing. Hence, it fills the gap in the existing literature by illustrating how ABC theory can be applied in the study relating to the ethical behaviour of accounting professionals.